Characteristics of acute groin injuries in the hip flexor muscles - a detailed MRI study in athletes - Serner, A.; Weir, A.; Tol, J. L.; Thorborg, K.; Roemer, F.; Guermazi, A.; Yamashiro, E.; Hölmich, P. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Hip flexor injuries account for one third of acute groin injuries; however, little is known about specific injury characteristics. The aims of this study was to describe acute hip flexor injuries using magnetic resonance imaging (MRI) in athletes with acute groin pain, and to compare specific muscle injuries with reported injury situations. Male athletes with acute groin pain were prospectively and consecutively included during 3 sports seasons. MRI was performed within 7 days of injury using a standardized protocol and a reliable assessment approach. All athletes with an MRI confirmed acute hip flexor muscle injury were included. 156 athletes presented with acute groin pain of which 33 athletes were included, median age 26 y (range 18-35). There were 16 rectus femoris, 12 iliacus, 7 psoas major, 4 sartorius, and 1 tensor fascia latae injury. Rectus femoris injuries primarily occurred during kicking (10) and sprinting (4), whereas iliacus injuries most frequently occurred during change of direction (5). In 10 (63%) rectus femoris injuries tendinous injury was observed. The iliacus and psoas major injuries were mainly observed at the musculotendinous junction (MTJ), and two included tendinous injury. We have illustrated specific injury locations within these muscles, which may be relevant for the clinical diagnosis and prognosis of these injuries. Most proximal rectus femoris injuries included tendinous injury. In contrast, distinct acute iliacus and psoas injuries predominantly occurred at the MTJ. Only the iliacus or psoas major were injured during change of direction, whereas rectus femoris injuries occurred primarily during kicking and sprinting.